1993
DOI: 10.1152/ajpheart.1993.265.5.h1516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glutamate stimulation of bed nucleus of the stria terminalis on arterial pressure and heart rate

Abstract: Experiments were done in the chloralose-anesthetized, paralyzed, and artificially ventilated rat to determine the cardiovascular responses elicited during chemical stimulation of bed nucleus of the stria terminalis (BST) and to investigate the components of the peripheral autonomic nervous system that mediate these responses. Neurons in BST were selectively stimulated by the microinjection (10-20 nl) of the excitatory amino acid L-glutamate (1 M). Stimulation of BST elicited decreases in mean arterial pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
3
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 0 publications
4
52
3
1
Order By: Relevance
“…In addition, the cardiovascular responses to stimulation of the PSTN returned to control levels ϳ20 min after the administration of CoCl 2 into mNTS. Furthermore, repetitive injections of Glu at the same PSTN site was found in this study to elicit cardiovascular responses that were both qualitatively and quantitatively similar, an observation that has been observed in previous studies following multiple Glu injections (8,13,16,27). It has also been previously reported that repeated injections of a low concentration of Glu, as used in this study, do not appear to have any significant neurotoxic affects (14,19).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In addition, the cardiovascular responses to stimulation of the PSTN returned to control levels ϳ20 min after the administration of CoCl 2 into mNTS. Furthermore, repetitive injections of Glu at the same PSTN site was found in this study to elicit cardiovascular responses that were both qualitatively and quantitatively similar, an observation that has been observed in previous studies following multiple Glu injections (8,13,16,27). It has also been previously reported that repeated injections of a low concentration of Glu, as used in this study, do not appear to have any significant neurotoxic affects (14,19).…”
Section: Discussionsupporting
confidence: 89%
“…The PSTN region was explored systematically on a grid pattern from 3.7 to 4.3 mm caudal to bregma, 1.3 to 2.2 mm lateral to the midline, and 7.0 to 8.2 mm ventral to the dorsal surface of the brain for sites that elicited changes in AP and/or HR. Solutions of Glu (0.25 M; 10 nl; Sigma, St. Louis, MO) (16) in 0.9% physiological saline were microinjected by the application of pressurized nitrogen pulses controlled by a picospritzer (General Valve, Fairfield, NJ) (8,16). The injected volume (10 nl) was measured by direct observation of the fluid meniscus in the micropipette by using a microscope fitted with an ocular micrometer that was calibrated to allow a 2-nl resolution.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations